Knowledge mapping of tumor microenvironment for breast cancer: a bibliometric analysis from 2014 to 2023 - Jiang, Dongping; Wen, Ping; Zhang, Senmiao; Zhang, Ningning; Shao, Qing; Wang, Guanwen; Wang, Long; Li, Sisi; Qin, Yang; Qu, Fanli; Zeng, Xiaohua (Frontiers in Immunology, 2025)
IntroductionBreast cancer is the most common malignant tumor among women worldwide, and the tumor microenvironment (TME) has become a hot research field in contemporary oncology. Understanding the TME is essential for elucidating the mechanisms of breast cancer progression and identifying novel therapeutic targets for metastasis and recurrence. This study performed a bibliometric analysis of TME research for breast cancer, providing a comprehensive overview of current research hotspots, development trends, and directions.MethodsWe retrieved for literature on TME for breast cancer published during 2014-2023 from the Web of Science database and performed bibliometric analysis. CiteSpace was used for co-citation analysis of references to assess the evolution and bursts in the knowledge base. VOSviewer was used for co-occurrence analysis of author keywords, countries/regions, institutions, and authors to reveal the knowledge structure and collaborative networks in this research area. Thematic evolution trends were analyzed using the bibliometrix package to reveal research hotspots, thematic evolution and dynamic changes of this research.ResultsA total of 9683 documents were included in this study, and the keyword co-occurrence analysis displayed five clusters: immunotherapy, metastasis, diagnosis and prognosis, metabolic regulation, and therapeutic approaches, with the first two keywords, immunotherapy and metastasis, being the most frequently mentioned. The most productive country/region, institution, and author were China (3266 publications), Shanghai Jiao Tong University (208 publications), and Takahashi, Kazuaki (37 publications).ConclusionIn breast cancer TME research, cancer-associated fibroblasts have attracted widespread attention, while cancer immunotherapy has emerged as a key focus in contemporary studies.